2012
DOI: 10.1097/ta.0b013e31820d1354
|View full text |Cite
|
Sign up to set email alerts
|

Operative management of periarticular medial clavicle fractures—Report of ten cases

Abstract: BACKGROUND:: The periarticular medial clavicle fracture is a rare injury and can be treated conservatively in the majority of cases. However, up to 8% of the patients develop symptomatic nonunion, and fracture dislocation correlates with the number of poor functional results. Operative treatment may be beneficial in these cases. Studies with large series of operated patients are still missing. METHODS:: We investigated 10 patients with operative treatment of periarticular medial clavicle fractures. Preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
90
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(90 citation statements)
references
References 14 publications
0
90
0
Order By: Relevance
“…However, because the medial fragment is usually small, it is difficult to achieve rigid fixation and early mobilization, and local stress at fracture site is high [1]. Hence, management of such injury is challenging for orthopedic surgeons.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, because the medial fragment is usually small, it is difficult to achieve rigid fixation and early mobilization, and local stress at fracture site is high [1]. Hence, management of such injury is challenging for orthopedic surgeons.…”
Section: Discussionmentioning
confidence: 97%
“…Historically, most medial clavicle fractures can be managed conservatively the exception to this being open fractures, soft damage, or associated neurovascular compromise [1]. However, recently clinical study showed that displaced medial clavicle fractures are associated with a symptomatic non-union rate of 8 % with conservative treatment [2].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Kim et al [24] reported successful surgical treatment of a displaced medial clavicle fracture using a small T-shaped plate and multiple tension band sutures. Oe et al [25] reporting the results of ten operatively treated medial clavicle fractures, recommended the use of locking plates, such as the T-locking plate or the pilon reconstruction plate, and highlighted the importance of at least three screw purchasing of the medial bone for rigid fixation.…”
Section: Discussionmentioning
confidence: 99%